Ezetimibe, cardiovascular risk and atherogenic dyslipidaemia - Rizzo, Manfredi (Termedia Publishing House, 2011)
Ezetimibe is a selective cholesterol absorption inhibitor with an excellent side-effect profile, able to reduce low-density lipoprotein (LDL) cholesterol by 15-25% from baseline in monotherapy and on top of statins and fibrates. Yet, it seems that ezetimibe produces quantitative rather than qualitative changes in LDL, with small net effects on atherogenic dyslipidaemia. This is supported by findings from the Ezetimibe and Simvastatin in Hypercholesterolemia Enhances Atherosclerosis Regression (ENHANCE) study on atherosclerosis progression, where the addition of ezetimibe to simvastatin in patients with heterozygous familial hypercholesterolaemia did not affect the mean change in carotid intima-media thickness, although a significant reduction in LDL cholesterol levels was observed. The Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study has further shown that combination treatment with simvastatin significantly reduced LDL cholesterol levels in patients with aortic stenosis, but did not affect the primary end point of aortic valve and cardiovascular events, although a significant reduction in the risk of ischaemic events was reported. Formal cardiovascular outcome trials are underway and these will provide additional insights into the long-term effects of ezetimibe on clinical events as well as on atherogenic dyslipidaemia, beyond LDL cholesterol levels.